Analisis Kendala dan Alternatif Solusi Andragogi dalam Praktikum Mengajar pada Program Studi Ekonomi Syariah - Dewi, Novi Rina; Baitulloh, Sabit; Umam, Muhammad Khoirul; Khoiron, Muhammad Zidni; Yuanida, Nisia; Mudawamah, Dewi; Fauziyah, Siti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to explore the application of andragogy principles in the context of teaching practicum in Islamic higher education. This research is expected to provide a comprehensive understanding of effective learning methods for students and the obstacles that can occur in other universities, as well as alternative solutions that can be considered in minimizing the obstacles experienced. This study uses a qualitative approach as a research method. Data collection was carried out during the teaching practicum with three ways of observation, interviews, and documentation to related parties. The learning methods used by Postgraduate practicum students of IAIN Kediri in andragogy include: 1) Lectures; 2) Discussion and Interaction; 3) Case Study; 4) Problem-Based Learning; 5) Collaborative Learning; 6) Technology-Based Learning; 7) Simulation or Demonstration. The main obstacles faced by IAIN Kediri Postgraduate students include: 1) Lack of Practicum Student Teaching Experience; and 2) Time Management. Alternative solutions offered in dealing with these practicum obstacles include: 1) Mastering Peembelajaran which is done by practicing and asking for advice; 2) Improve Time Management Skills